Practical neuroophthalmology - Martin, Timothy J. (McGraw-Hill Education/Medical, 2013)
This book covers the basic principles and major conditions of neuroophthalmologyin a concise, user-friendly manner. Rather than merely presenting a catalog of facts, the authors enrich the text by describing how complex neuroophthalmic signs and symptoms are often a logical consequence of anatomy and pathophysiology.